Analyzing the impact of the innovation performance on high-tech enterprises: a case study of the Chinese semiconductor industry - Yin, Feng; Lee, Woonseek; Guo, Yaoyao (Journal of Business Economics and Management, 2024)
This study, which focuses on Chinese semiconductor companies, explores the relationship between government support (GS), proactive market orientation (PMO), science and technology (S&T) employees input (STEI), S&T employees management (STEM), and innovation performance (IP). In addition, existing studies examine the moderating effect of S&T employees management (STEM) on the relationship between S&T employees input (STEI) and innovation performance (IP). We obtained 324 valid samples through an email survey and utilized structural equation modeling (SEM) path analysis for hypothesis testing. The results of the analysis indicated that government support (GS), proactive market orientation (PMO), S&T employees input (STEI), and S&T employees management (STEM) exerted a positively significant effect on innovation performance. However, the moderating effect of S&T employees management on S&T employees input and innovation performance was not validated. Based on these findings, it can be concluded that Chinese semiconductor companies should utilize preferential policies of government offer. By adopting a proactive market orientation, companies can enhance communication with customers and can gain competitive advantage. In addition, enterprises should increase the number of S&T employees, and salaries and training costs. Finally, enterprises should implement the human resources strategy which can retain outstanding S&T employees.